Minat Baca Praja Terhadap Buku Novel Di Perpustakaan IPDN Kampus Nusa Tenggara Barat - Muh. Muaidi (THE LIGHT : Journal of Librarianship and Information Science, 2022)
Reading interest can be seen from the level of wearability of the collection. For this reason, it is necessary toresearch how frequency the library collections use. The purpose of this study is to find out the student's readinginterest in novel books related to the use of novel collections at the Library Unit of IPDN NTB Campus, fromJuly 2019 to December 2020. In this study, the researcher used a descriptive method, namely by describingaccurate data regarding the facts, the nature of the relationship between the phenomena under study. The resultsof this study indicate that the number of novel collections are 61 titles with 326 copies. The number of usabilityof the novel collections in the IPDN Library of the NTB Campus from July to December 2019 reached 384 books(117.79%). While the usability of the novel collection from January to December 2020 are 97 books (29.75%).There was a decrease in the usability of novel books reaching 287 books (88.04%). Minister of Home AffairsRegulation number 21 of 2020 concerning Large-Scale Social Restrictions (PSBB) triggered a drastic decreasein the use of novel book collections at the IPDN Library, NTB Campus.